Unusual cause of lumbar pain in elite sports: Two case reports of sacral stress fractures - Hoffmann, F.; Heinz, L.; Mouton, C.; Seil, R.; Nührenbörger, C. (Deutsche Zeitschrift für Sportmedizin, 2022)
Summary